Women’s perception on medicinal plants in traditional Tamu, West Coast, Sabah, Malaysia - Jurry Foo; A. LATIFF; MUSTAFA OMAR; AHMAD ALDRIE AMIR (Malaysian Nature Society, 2016)
The objective of this paper is to describe the perception among women on the medicinal plants they sold in the tamu (local market) in West Coast, Sabah. The study was conducted in 14 selected tamu. Related information has been collected through questionnaires and interviews with 84 women involved as respondents. Data were analyzed using descriptive statistical analysis in IBM SPSS software 21. Finding showed that the majority of the items showed a high score, except for two items listed below mean score of 3.68, which are at a moderate level. The average mean score is 4.06, which means the perception of women on the sale of medicinal plants is positive and at a high level.